Interaction design : beyond human-computer interaction - Rogers, Yvonne; Preece, Jennifer , 1949-; Sharp, Helen (Wiley, 2011)
"A revision of the #1 text in the Human Computer Interaction field, Interaction Design, the third edition is an ideal resource for learning the interdisciplinary skills needed for interaction design, human-computer interaction, information design, web design and ubiquitous computing"-- Provided by publisher